The Travails of Postgraduate Research in Law - Arlie Loughnan; Rita Shackel (Legal Education Review)
This article identifies key task variables that can be manipulated in ways appropriate to the assessment of student learning at different stages in their progression from ‘novice’ to ‘expert’legal practitioner. The ideas presented elaborate on the outcomes of a symposium discussion of the systematic assessment of law students’ abilities to undertake a variety of professional roles. The symposium was organised by the Council of Australian Law Deans (CALD) as part of a project funded by the Australian Learning and Teaching Council (ALTC). After a general introduction to the structure and design of individual assessment tasks, the key dimensions of such tasks are identified and possible modifications illustrated with reference to specific examples.